The Importance of Halal Certificates in Halal Food Using the Digital Platform - Nurillah, Shinta Lintang (International Journal of Law Dynamics Review, 2023)
The world's fast progress, particularly in the realm of technology, necessitates the adaptation of diverse sectors to current developments. The COVID-19 epidemic has had a minimal influence on communal activities as a result of the Indonesian government's strategy of imposing large-scale social restrictions. Restrictions have an influence not just on the major company sector, but also on the small and medium enterprise (MSME) sector. The COVID-19 epidemic has become a new issue for MSMEs in the midst of business innovation rivalry and the need to think of other solutions to continue selling, even if only from home. The fast evolution of digital technology is the outcome of efforts to fulfill human life's requirements. The basic essentials of existence are food. According to Article 29 of the Republic of Indonesia's 1945 Constitution, "the State guarantees every citizen to embrace their respective religions and to worship according to their religion and beliefs." As a result, the state is obligated to give assurances and safeguards for the halalness of the items ingested. The Halal Product Assurance Agency (BPJPH) of the Ministry of Religion of the Republic of Indonesia provides product halal assurance by offering free halal certification (self-declaration) services. According to the outcomes of the conversation, the government has established a strategy to increase halal certification through the halal self-declaration program. The initiative is still in its early stages and requires extensive socialization across all divisions of industry, particularly among those who utilize digital platforms.